Bolstering the Three Pillars of the Essential Architecture of the Massage Therapy Profession: An Interview with Glenn M. Hymel, EdD, LMT - Kennedy, LMT, BCTMB, DrPH, Ann Blair (International Journal of Therapeutic Massage & Bodywork, 2018)
As part of our interview editorial series, we bring forth a discussion with Dr. Glenn M. Hymel, the Founding Executive Editor of the International Journal of Therapeutic Massage and Bodywork. Dr. Hymel embodies the qualities set forth for the American Massage Therapy Association Dianne Polseno Lifetime Achievement Award, which he received in 2017. He has provided leadership and shown outstanding professionalism, and is a dedicated volunteer and a fervent advocate for research and education in the massage therapy profession. In this interview he discusses his massage therapy research, his interests, and his hopes for the future and the profession.